Cytotoxicity difference of 316L stainless steel and titanium reconstruction plate - Ni Putu Mira Sumarta; Coen Pramono Danudiningrat; Ester Arijani Rachmat; Pratiwi Soesilawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Pure titanium is the most biocompatible material today and used as a gold standard for metallic implants. However, stainless steel is still being used as implants because of its strength, ductility, lower price, corrosion resistant and biocompatibility. Purpose: This study was done to revealed the cytotoxicity difference between reconstruction plate made of 316L stainless steel and of commercially pure (CP) titanium in baby hamster kidney-21 (BHK-21) fibroblast culture through MTT assay. Methods: Eight samples were prepared from reconstruction plates made of stainless steel type 316L grade 2 (Coen’s reconstruction plate®) that had been cut into cylindrical form of 2 mm in diameter and 3 mm long. The other one were made of CP titanium (STEMA Gmbh®)) of 2 mm in diameter and 2,2 mm long; and had been cleaned with silica paper and ultrasonic cleaner, and sterilized in autoclave at 121° C for 20 minutes.9 Both samples were bathed into microplate well containing 50 μl of fibroblast cells with 2 x 105 density in Rosewell Park Memorial Institute-1640 (RPMI-1640) media, spinned at 30 rpm for 5 minutes. Microplate well was incubated for 24 and 48 hours in 37° C. After 24 hours, each well that will be read at 24 hour were added with 50 μl solution containing 5mg/ml MTT reagent in phosphate buffer saline (PBS) solutions, then reincubated for 4 hours in CO2 10% and 37° C. Colorometric assay with MTT was used to evaluate viability of the cells population after 24 hours. Then, each well were added with 50 μl dimethyl sulfoxide (DMSO) and reincubated for 5 minutes in 37° C. the wells were read using Elisa reader in 620 nm wave length. Same steps were done for the wells that will be read in 48 hours. Each data were tabulated and analyzed using independent T-test with significance of 5%. Results: This study showed that the percentage of living fibroblast after exposure to 316L stainless steel reconstruction plate was 61.58% after 24 hours and 62.33% after 48 hours. And after exposure to titanium reconstruction plate, the percentage of living fibroblast was 98.69% after 24 hours and 82.24% after 48 hours. Based on cytotoxicity parameter (CD50%), both reconstruction plate made of 316L stainless steel or titanium showed as a non-toxic materials to fibroblast. Conclusion: Both reconstruction plate made of stainless steel and CP titanium were non-toxic to fibroblast, although the stainless steel plate showed lower cytotoxicity level compared to titanium. Therefore a reconstruction plate made from stainless steel type 316L can be used as a safe material for mandibular reconstruction. Latar belakang: Titanium murni adalah bahan yang paling biokompatibel saat ini dan digunakan sebagai standar emas implan logam. Saat ini stainless steel masih digunakan karena kekuatan, ductility, harganya yang murah, tahan terhadap korosi dan cukup biokompatibel. Tujuan: Penelitian ini dilakukan untuk mengetahui perbedaan sitotoksisitas antara plat rekonstruksi yang terbuat dari titanium murni komersial dan plat rekonstruksi yang terbuat dari stainless steel pada kultur sel fibroblas baby hamster kidney-21 (BHK-21) menggunakan MTT assay. Metode: Delapan sampel yang masing-masing tipe 316L terbuat dari stainless steel 316L grade 2 (Coen’s reconstruction plate®) yang dipotong berbentuk silinder diameter 2 mm dan panjang 3 mm, serta yang terbuat dari titanium murni komersial (STEMA Gmbh®) diameter 2 mm dan panjang 2,2 mm; dan dibersihkan dengan kertas silika dan pembersih ultrasonik serta disterilkan dengan autoclave pada suhu 121° C selama 20 menit. Kedua sampel dimasukkan ke dalam sumur mikroplat yang mengandung 50 μl sel fibroblas dengan kepadatan 2 × 105 dalam media Rosewell Park Memorial Institute-1640 (RPMI-1640), diputar dengan kecepatan 30 rpm selama 5 menit. Sumur mikroplat diinkubasi selama 24 dan 48 jam pada suhu 37° C. Setelah 24